Climate adaptation in urban space: the need for a transdisciplinary approach - Lenzi, Sara; Sádaba, Juan; Retegi, Aiur (Frontiers in Sustainable Cities, 2025)
Climate change demands innovative and holistic approaches to urban design that address both the tangible and intangible challenges posed by a rapidly evolving environment. This article explores the necessity of a transdisciplinary approach to climate adaptation in urban spaces, emphasizing the integration of architecture, social innovation, more-than-human design, and multisensory analysis. We examine the current approaches and controversies of architectural and urban solutions to climate adaptation. Drawing on the state-of-the-art from key fields, we discuss the potential of Nature-based Solutions, co-creation practices, and multimodal design to create adaptive urban spaces that address the physical, emotional, and social needs of human and more-than-human inhabitants. The article reviews emerging frameworks and case studies, including climate shelters, biodiversity-inclusive design, and the integration of soundscapes and smellscapes, to demonstrate the importance of considering diverse perspectives and stakeholders. By synthesizing these findings, we propose an integrated design framework for climate adaptation that moves beyond traditional architectural approaches by overlapping intangible layers of social awareness, ecological diversity, and cultural sensitivity.